Approaching Laestadianism as an insider researcher - Snellman, Gerd (Approaching Religion, 2020)
In this article, I discuss my experiences of being an insider researching Laestadianism. I present my research, noting the advantages and disadvantages, ending with a conclusion in which I refer to the discussion among anthropologists and ethnologists, especially in the study of religion. The outcome is that even though the distinction insider–outsider researcher is complicated, both insider and outsider researchers will improve the research, contributing to its nuanced presentation.